A HUMAN RESOURCE MANAGEMENT MODEL ENTREPRENEURSHIP BASED ON THE QUALITY OF EDUCATIONAL INSTITUTIONS - Iwan Saputra; Ricky Hermayanto; Yanti Hidayanti (LKP DCI, 2024)
In education , management model management source Power man is something encouragement For maximizing efficiency and effectiveness in increase quality so that input, process and output can be achieved and implemented , encouragement the is A utilization from source Power humans ( Educators and Educators ) . study This aim For know what is the HR and school management model based entrepreneurship its influence to quality institution education at Serba Bakti Islamic Middle School. Study This use mixed methods . Population study This are 32 teachers and staff at Serba Bakti Suryalaya Islamic Middle School Where the whole made sample in study . Data obtained use questionnaires , interviews and observations . results study showing that management model source Power people and school programs based entrepreneurship Good in a way Partial nor simultaneous influential to quality institution education at Serba Bakti Islamic Middle School.